PROSEDUR PELAKSANAAN DEPOSITO BERJANGKA PADA PT BPR BARELANG MANDIRI KC TEMBESI - Chris Melyn S; Hajan Hidayat (PT Aksara Indo Rajawali, 2022)
This study report discusses the procedure for implementing time deposits at PT BPR Barelang Mandiri. The purpose of this research is to create and compile Standard Operating Procedures for Time Deposits in accordance with the banking application system that applies at PT BPR Barelang Mandiri KC Tembesi. This study uses data that has been analyzed using descriptive methods and the method of data collection is carried out by interview and documentation techniques. The results of the study stated that the Standard Operating Procedures were not in accordance with the applicable Application System so that implementation errors were found between Customer Service and related Marketing which caused losses to customers.